1981
DOI: 10.1139/x81-035
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of temperature control of production and nutrient cycling in two interior Alaska black spruce ecosystems

Abstract: Selected indices of structure and function were used to evaluate the effect of differing soil thermal regimes on soil-permafrost-dominated (muskeg) and permafrost-free (north-slope) black spruce ecosystems in interior Alaska. The poorly drained, permafrost site displayed cooler soil temperatures and higher soil moisture content than were encountered on the well-drained north slope. Mineral soil nutrient pools generally were largest on the permafrost site. However, low soil temperature acted as a negative feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 0 publications
1
33
1
Order By: Relevance
“…A higher alkyl: O-alkyl ratio is consistent with the increased decomposition extent commonly observed in warmer, south facing soils in boreal black spruce forests (Van Cleve et al 1981, 1983Kane et al 2005; see also Wickland and Neff 2008). The greater extent of decomposition in south-facing soils was also reflected in higher organic layer bulk densities and shallower organic layer depths ( Fig.…”
Section: Interactions Among Landscape Position and Soc Propertiessupporting
confidence: 81%
“…A higher alkyl: O-alkyl ratio is consistent with the increased decomposition extent commonly observed in warmer, south facing soils in boreal black spruce forests (Van Cleve et al 1981, 1983Kane et al 2005; see also Wickland and Neff 2008). The greater extent of decomposition in south-facing soils was also reflected in higher organic layer bulk densities and shallower organic layer depths ( Fig.…”
Section: Interactions Among Landscape Position and Soc Propertiessupporting
confidence: 81%
“…Letters indicate statistical differences among harvest treatments tested individually for each species factor influencing mass loss (greater mass loss at 10 cm than at >20 cm) other than substrate type. While temperature was not measured in this study, previous work has consistently shown that deep soil layers were cooler and more humid than shallow soil layers (Van Cleve et al 1981;Klenk 2001;Simard et al 2007) and this was probably the cause of the lower mass loss at the >20 cm depth, as temperature is one of the main driving forces in nutrient cycling in boreal forests (Van Cleve et al 1981).…”
Section: Discussionmentioning
confidence: 64%
“…This absence of a significant relationship may be due to the relatively low nutritional requirements of conifers (Munson and Timmer 1989), compared with those of species such as Prunus pensylvanica L. (Jobidon 1995) for which such a relation was observed on sites subjected to conventional windrowing, without exporting organic matter (McCavour et al 2014). In fact, the characteristics of the litter and the cold, humid climate of the boreal forest slow down organic matter mineralization (Van Cleve et al 1981, Van Cleve et al 1990, Scott and Binkley 1997, Pajuste and Frey 2003. Therefore, nutrients accumulated in windrows would certainly require several years to be re-circulated (Blumfield et al 2004).…”
Section: Discussionmentioning
confidence: 99%